Deterioration of symbiont bearing morozovellid habitat (planktic foraminifera) habitat recorded within the Early Eocene Climatic Optimum: evidence from the Tethys and sub-tropical Atlantic Ocean - LUCIANI, Valeria; D'ONOFRIO, Roberta; Giusberti L.; Fornaciari E.; Rio D.; Backman J. (Rendiconti online della Società Geologica Italiana, 2014)
The Early Eocene Climatic Optimum (EECO) is the crucial interval of the Cenozoic climate recording the highest global temperatures of the past 70 Ma, followed by a long-term cooling ultimately leading to the emplacement of a stable ice sheet on Antarctica. The early Paleogene section of Possagno (Venetian Prealps of northeastern Italy), deposited in a bathyal setting, provides an excellent magneto- and calcareous plankton stratigraphic record of the lower-middle Eocene transition as occurring in a marginal basin of the central-western Tethys (~55 to 46 Ma). This section therefore spans the EECO interval. Only a few studies have focused on paleoecological and evolutionary consequences of the EECO on planktic foraminifera. We show that morozovellids, a main group of early Paleogene calcifiers record a first critical step across the EECO because they record a permanent, marked decline in abundance from the Tethys (Possagno section) and North Atlantic Ocean (ODP Site 1051) realms.